Systemic Thrombolytic Therapy for Acute Pulmonary Embolism: Who Is a Candidate? - Konstantinides, Stavros V.; Barco, Stefano (Seminars in Respiratory and Critical Care Medicine, 2017)
Pulmonary embolism (PE) is a major cause of both acute and long-term morbidity for a large number of patients worldwide, and massive PE is frequently fatal. Right ventricular (RV) dysfunction is a key determinant of prognosis in the acute phase of PE. Patients with clinically overt RV failure, that is, with cardiogenic shock or persistent hypotension at presentation (acute high-risk PE), are clearly in need of immediate reperfusion treatment with systemic thrombolysis or, alternatively, surgical or catheter-directed techniques. On the other hand, within the large group of patients presenting without hemodynamic instability, the bleeding risk of full-dose intravenous thrombolytic treatment has been shown to outweigh its benefits, even if they present with evidence of both RV dysfunction and myocardial injury. Thus, current guidelines agree in proposing a strategy of effective anticoagulation and “watchful waiting” (with initial hemodynamic monitoring notably over the first 48–72 hours) in intermediate-risk PE, with an indication for rescue thrombolysis if signs of hemodynamic decompensation appear. Recently published trials suggest that catheter-directed, ultrasound-assisted, low-dose local fibrinolysis may provide an effective and particularly safe treatment option for some of these patients. Ongoing or planned studies are expected to resolve the controversy on the efficacy and safety or reduced-dose systemic thrombolysis and to address the possible impact of thrombolytic therapy on long-term outcomes after acute PE.
Keywords: pulmonary embolism; thrombolysis; risk stratification; guidelines; intravenous; catheter-directed; bleeding; chronic thromboembolic pulmonary hypertension